Shock to the system : coups, elections, and war on the road to democratization - Miller, Michael Keith, 1981- (Princeton University Press, 2021)
How violent events and autocratic parties trigger democratic changeHow do democracies emerge? Shock to the System presents a novel theory of democratization that focuses on how events like coups, wars, and elections disrupt autocratic regimes and trigger democratic change. Employing the broadest qualitative and quantitative analyses of democratization to date, Michael Miller demonstrates that more than nine in ten transitions since 1800 occur in one of two ways: countries democratize following a major violent shock or an established ruling party democratizes through elections and regains power within democracy. This framework fundamentally reorients theories on democratization by showing that violent upheavals and the preservation of autocrats in power--events typically viewed as antithetical to democracy--are in fact central to its foundation. Through in-depth examinations of 139 democratic transitions, Miller shows how democratization frequently follows both domestic shocks (coups, civil wars, and assassinations) and international shocks (defeat in war and withdrawal of an autocratic hegemon) due to autocratic insecurity and openings for opposition actors. He also shows how transitions guided by ruling parties spring from their electoral confidence in democracy. Both contexts limit the power autocrats sacrifice by accepting democratization, smoothing along the transition. Miller provides new insights into democratization's predictors, the limited gains from events like the Arab Spring, the best routes to democratization for long-term stability, and the future of global democracy. Disputing commonly held ideas about violent events and their effects on democracy, Shock to the System offers new perspectives on how regimes are transformed.
Keywords: Democratization.; New democracies.; Political violence.; Elections.; Démocratisation.; Nouvelles démocraties.; Violence politique.; Élections.; terrorism.; elections.; POLITICAL SCIENCE -- Political Ideologies -- Democracy.; Democratization; Elections; New democracies; Political violence; Aftershocks.; Bolivia.; Brazil.; Democratic Coup D'Etat.; Falklands War.; Fiji.; Greece.; James Loxton.; Lucan Way.; Ozan Varol.; Portugal.; Rachel Riedl.; Robert Kaufman.; Ruth Collier.; Samuel Huntington.; Scott Mainwaring.; Seva Gunitsky.; Stephen Haggard.; Steven Levitsky.; Taiwan.; authoritarianism.; autocracy.; autocratic elections.; autocratic institutions.; democratic erosion.; democratic opponents.; democratic survival.; dictatorship.; electoral continuity.; international war.; leader insecurity.; political economy.; prodemocratic activity.; protest.; spring of nations.; war.